2020
DOI: 10.1371/journal.pone.0243051
|View full text |Cite|
|
Sign up to set email alerts
|

Impact of disease stage and age at Parkinson’s onset on patients’ primary concerns: Insights for targeted management

Abstract: Background The concerns of people with Parkinson’s disease (PD) about their disease are often different from the objective clinical picture and subject to various influencing factors, including disease progression. Currently our understanding of these concerns is limited, particularly in Asian countries. Methods A 50-item survey on Parkinson’s Disease Patients’ Concerns (PDPC Survey) was developed by a multidisciplinary care team. The subjective greatest concerns (most commonly concerning symptoms) of patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…From a patient's perspective, difficulty in getting out of bed is their most common concerning motor symptom, representing a common functional limitation that is negatively associated with the patient's quality of life ( 9 , 19 , 25 , 26 ). From a carer's perspective, getting out of bed is the most frequent activity that patients require assistance from them to achieve and increases carer's burden ( 18 , 53 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…From a patient's perspective, difficulty in getting out of bed is their most common concerning motor symptom, representing a common functional limitation that is negatively associated with the patient's quality of life ( 9 , 19 , 25 , 26 ). From a carer's perspective, getting out of bed is the most frequent activity that patients require assistance from them to achieve and increases carer's burden ( 18 , 53 ).…”
Section: Discussionmentioning
confidence: 99%
“…While the evidence is clear that nocturnal hypokinesia, when considered as a whole, negatively affects sleep quality, sleep efficiency, and quality of life of patients with PD ( 15 , 16 ), difficulty in getting out of bed, as an isolated symptom, was rated as an emerging disability amongst patients with PD after a 2-year subsequent follow-up, and was the most frequent activity of daily living (ADL) to be assisted by carers of patients with PD ( 17 , 18 ). Similarly, another separate study identified the problem of getting out of bed as a factor associated with the presence of a carer, and it was rated by 39.6% of the patients with PD as their commonly concerning motor symptoms ( 19 ). When getting out of bed is considered as a spectrum of early morning off (EMO), it was found to be very common, affecting 72.4% of patients with PD, with bradykinesia or rigidity and fatigue or sleepiness the most common motor and non-motor symptoms, respectively ( 20 ).…”
Section: Introductionmentioning
confidence: 99%
“…Many patients with PD are most bothered by the perception that others might have of their impairment than by their impairment itself. 141,142 This higher level of stigma in patients with EOPD 17,143 seems to stem essentially from dysarthria, tremor, dyskinesia, and impact of the motor symptoms on activities of daily living such as eating and washing 144 and can manifest as a reluctance to seek help and ask for adjustments at work, which in turn decreases the chances of staying employed.…”
Section: Impact Of Pd On Employment and Social Perceptionmentioning
confidence: 99%
“…In a prospective 50-item survey aimed at clarifying patients' concerns in 222 individuals with PD, patients with EOPD (AAO < 50) reported significantly more concerns about difficulty with speaking (P = 0.003), washing and bathing (P = 0.04), or eating (P = 0.003) as well as with shaking (P = 0.005), dyskinesia (P = 0.001), low and/or depressed mood (P = 0.01), and anxiety and/or panic attacks (P < 0.001)factors more likely to impact social or professional functioningas greater concerns than typical-onset patients with PD. 144 Finally, EOPD may present a challenge to relationships. Marriages or relationships of shorter duration can be more vulnerable to the strain a chronic illness can impose than those of longer duration, 145 with significantly worse marital discord scores in couples with EOPD than in those with LOPD in 1 study comparing 75 patients with EOPD (<50 years) and 66 patients with LOPD.…”
Section: Impact Of Pd On Employment and Social Perceptionmentioning
confidence: 99%
“…While there are no dedicated studies that determine the need of AT in patients with tremor, it is, as they are predominantly elderly, our own view that many of these barriers are likely to influence the adoption of AT in these patients. In a separate study that explored the need of AT in patients with PD, a shower chair was considered the most needed device (38.3%), followed by almost the same number of patients who reported the need for a walking stick (36.5%), and anti-slip mat (34.7%) [78]. However, AT for tremor (tremor suppression spoon and gloves) was considered as needed by only 7% of PD patients, which may reflect the abovementioned barriers, coupled to a lack of awareness by both patients and healthcare professionals, or lack of recommendation by treating physicians.…”
Section: Implementing Assistive Devices In Patients With Tremor: Cons...mentioning
confidence: 99%